Research thoughts on the education of reaching old age and the ageing process = Myśli badawcze o/dla edukacji do starości i nad procesem starzenia się - Kowalski, Mirosław; Śliwa, Sławomir (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The theoretical and cognitive aim of the research was to find out the opinions and knowledge of teachers in the field of education about old age. The research was carried out among 106 teachers from primary schools in the Opolskie Voivodeship using the diagnostic survey method, the questionnaire technique.
Keywords: old age education; old age; st and 2nd stage of education; edukacja do starości; starość; I i II etap edukacyjny